Analisis Evaluasi Model Cipp pada Pengelolaan Sumber Daya Manusia - Arina Manasikana; Triana Rosalina Noor (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2025)
This study aims to analyze human resource management at SDN Tambak Wedi 508 Surabaya using the CIPP (Context, Input, Process, Product) evaluation model during the 2024-2025 academic year. The research method employed is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies. The research subjects include the school principal, teachers, and administrative staff. The results show that: (1) Context evaluation describes the alignment of HR management programs with the school's vision, mission, and objectives; (2) Input evaluation identifies the availability of human resources, infrastructure, and budget in supporting HR management programs; (3) Process evaluation analyzes the implementation of teacher and staff competency development programs, recruitment systems, and performance evaluations; (4) Product evaluation demonstrates improvements in teacher and staff performance quality, as well as their impact on student achievement. This study recommends the need for developing continuous training programs and a more structured monitoring and evaluation system to enhance the effectiveness of HR management in schools.